Stereoscopy in diagnostic radiology and procedure planning: Does stereoscopic assessment of volume‐rendered CT angiograms lead to more accurate characterisation of cerebral aneurysms compared with traditional monoscopic viewing?. Issue 2 (14th February 2014) - Stewart, Nikolas; Lock, Gregory; Hopcraft, Anthony; Kanesarajah, Jeeva; Coucher, John
Abstract Introduction Stereoscopic vision is a critical part of the human visual system, conveying more information than two‐dimensional, monoscopic observation alone. This study aimed to quantify the contribution of stereoscopy in assessment of radiographic data, using widely available three‐dimensional (3D)‐capable display monitors by assessing whether stereoscopic viewing improved the characterisation of cerebral aneurysms. Methods Nine radiology registrars were shown 40 different volume‐rendered (VR) models of cerebral computed tomography angiograms (CTAs), each in both monoscopic and stereoscopic format and then asked to record aneurysm characteristics on short multiple‐choice answer sheets. The monitor used was a current model commercially available 3D television. Responses were marked against a gold standard of assessments made by a consultant radiologist, using the original CT planar images on a diagnostic radiology computer workstation. Results The participants' results were fairly homogenous, with most showing no difference in diagnosis using stereoscopic VR models. One participant performed better on the monoscopic VR models. On average, monoscopic VRs achieved a slightly better diagnosis by 2.0%. Conclusions Stereoscopy has a long history, but it has only recently become technically feasible for stored cross‐sectional data to be adequately reformatted and displayed in this format. Scant literature exists to quantify the technology's possible contribution to medical imaging – this study attempts to build on this limited knowledge base and promote discussion within the field. Stereoscopic viewing of images should be further investigated and may well eventually find a permanent place in procedural and diagnostic medical imaging.